2013
DOI: 10.1108/jidob-03-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of male autistic spectrum patients in low security: are they different from non‐autistic low secure patients?

Abstract: Purpose -The purpose of this paper is to describe the characteristics of adult male autistic spectrum disorder (ASD) patients admitted to low secure services and to compare them with non-ASD patients. Design/methodology/approach -Case-control study of admissions to two ASD units and one non-ASD unit at a tertiary referral centre. Subjects were compared on demographic, personal, clinical and offending behaviour variables. Findings -In total, 51 ASD and 43 controls were studied. Median age at diagnosis of ASD wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…In a Swedish study of young offenders referred for forensic assessment: 15% had ASD with further 12% having probable ASD (Siponmaa et al, 2001), a US study in a maximum secure prison found that 4.4% of participants had significant ASD traits (Fazio et al, 2012) and Hare and colleagues (1999) found an ASD rate of 2.4% in three high secure hospitals in England while a study in the Scottish prison service found a rate of just 0.93% (Robinson et al 2012). Haw et al (2013) looked at the characteristics of male patients in a low secure setting with ASD. Compared with those without ASD, they were more likely to be single, at a younger age at their first contact with psychiatric services and 73% had a psychiatric diagnosis (most commonly schizophrenia) but personality disorders and substance abuse were less common.Studies of ASD among forensic populations have produced mixed results (Sabet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a Swedish study of young offenders referred for forensic assessment: 15% had ASD with further 12% having probable ASD (Siponmaa et al, 2001), a US study in a maximum secure prison found that 4.4% of participants had significant ASD traits (Fazio et al, 2012) and Hare and colleagues (1999) found an ASD rate of 2.4% in three high secure hospitals in England while a study in the Scottish prison service found a rate of just 0.93% (Robinson et al 2012). Haw et al (2013) looked at the characteristics of male patients in a low secure setting with ASD. Compared with those without ASD, they were more likely to be single, at a younger age at their first contact with psychiatric services and 73% had a psychiatric diagnosis (most commonly schizophrenia) but personality disorders and substance abuse were less common.Studies of ASD among forensic populations have produced mixed results (Sabet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Only three studies explored any type of characteristics of patients with ASD detained in secure psychiatric hospitals (Murphy, 2003;Haw, Radley, & Cooke, 2013;Murphy, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Haw and colleagues' study, there was no significant difference between the controls and the patients with ASD in terms of history of antisocial behaviour before the age of 18 years, age of first conviction and having served a custodial sentence. Patients with ASD did, however, have less prior convictions compared to the controls but this could be because of the age difference between the two groups (Haw et al, 2013).…”
Section: Characteristics Of Patients With Asd Detained In Secure Psycmentioning
confidence: 99%
See 2 more Smart Citations